Labor market consequences of the college boom around the world - Gustavo Yamada; Pablo Lavado (IZA World of Labor, 2018)
As the number of secondary school graduates rises, many developing countries expand the supply of public and private universities or face pressure to do so. However, several factors point to the need for caution, including weak job markets, low-quality university programs, and job–education mismatches. More university graduates in this context could exacerbate unemployment, underemployment, and overeducation of professionals. Whether governments should regulate the quantity or quality of university programs, however, depends on the specific combination of factors in each country.
Keywords: J20; J23; J24; J38; 330; underemployment; university professionals; skilled labor; overeducation; higher education; educational mismatch